ASOCIACIONES DE OSTRÁCODOS DEL MIOCENO TEMPRANO–MEDIO DE LOMA NEGRA (BARDENAS REALES DE NAVARRA, CUENCA DEL EBRO): EVOLUCIÓN PALEOAMBIENTAL DE UN MEDIO LACUSTRE (Ameghiniana, 2014)
The palaeoenvironmental evolution of theLoma Negra section (Bardenas Reales de Navarra, Ebro Basin) during the lower–middle Miocene, is studied for the first time. The paleoenvironmentalinterpretationis based on the recoveredostracod assemblages and the sedimentology.Thelowerpartof this sectionis composedbyred,yellowand greymudstones, and with Paralimnocytheresp. as the most abundant ostracod taxon. The lithological features and the faunisticassemblage allowsthe interpretationof a paleoenvironmentwith the developmentof shallowwater bodies with stagnant, warmandfreshto oligohaline waters in distal alluvial flood plains for this section. Thepresenceof some sandstone levelswherethe mostabundant ostracodspecies is Cyclocyprislaevis (Müller)markspunctual higher energy eventsinside this alluvial system and the presenceof moresalinewaters.Theupper partof the section is formed bygreylimestones with interbedded fine greymudstones. Inthis interval,PseudocandonaparallelaMüller is the most abundant ostracod species, indicating the development of a stable lacustrine system with water currents, and temperateto cold and oligohaline to mesohaline waters. Thetransition betweenthe alluvial and the lacustrine systems showsa gradualevolution.